1999
DOI: 10.1017/s0031182099004825
|View full text |Cite
|
Sign up to set email alerts
|

IgG reactivities against recombinant Rhoptry-Associated Protein-1 (rRAP-1) are associated with mixed Plasmodium infections and protection against disease in Tanzanian children

Abstract: A cross-sectional sero-epidemiological study was performed in Magoda, Tanzania, an area where malaria is holoendemic. Blood samples were collected from children (1-4 years) and tested for IgG antibody reactivity against 2 recombinant protein fragments of Plasmodium falciparum Rhoptry-Associated Protein-1 (rRAP-1). The data were related to the prevalence of malarial disease and single P. falciparum or mixed Plasmodium infections. Fever (> or = 37.5 degrees C) in combination with parasite densities > 5000/microl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
1
19
1
Order By: Relevance
“…In other studies, P. falciparum - P. vivax mixed infections affected the clinical outcome in patients [13,16]. Examples of P. malariae and P. ovale co-infections with P. falciparum protecting against malaria symptoms have also been reported [17]. Studies with a Plasmodium berghei and Plasmodium yoelii co-infection model in mice appear to confirm that there can be a strong cross-protective effect of mixed species infections [18].…”
Section: Introductionmentioning
confidence: 92%
“…In other studies, P. falciparum - P. vivax mixed infections affected the clinical outcome in patients [13,16]. Examples of P. malariae and P. ovale co-infections with P. falciparum protecting against malaria symptoms have also been reported [17]. Studies with a Plasmodium berghei and Plasmodium yoelii co-infection model in mice appear to confirm that there can be a strong cross-protective effect of mixed species infections [18].…”
Section: Introductionmentioning
confidence: 92%
“…Naturally acquired antibodies recognize linear epitopes in RAP1 and RAP2 [218]. Human antibodies against RAP1 are associated with protection against malaria [219][220][221]. Another rhotry antigen RAMA has been shown to bind the erythrocyte membrane during invasion [222].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Some studies have reported a lower rate of severe disease in infection with both P. falciparum and P. vivax than in infection with P. falciparum only. Clinical symptoms such as anemia, fever, and parasitemia may occur less frequently or to lower degrees in mixed infection than in monospecies infection [14]. However, contradictory findings have also been reported [5].…”
Section: Discussionmentioning
confidence: 99%